2021
DOI: 10.3390/polym13213694
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Toothbrush Abrasion and Surface Treatments on Roughness and Gloss of Polymer-Infiltrated Ceramics

Abstract: The aim of this study was to compare the surface roughness and gloss of polymer-infiltrated ceramics after simulated in vitro toothbrushing in different storage mediums. Four polymer- infiltrated ceramics were evaluated, Lava ultimate (LU), Vita enamic (EN), Shofu (SH), and Crystal ultra (CU). The control group was a feldspathic ceramic, Vita Mark II (VM). One hundred and twenty specimens (12 × 14 × 2.5 mm) were prepared using a precision saw. For each material (n = 24), the specimens were allocated into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
8
0
4
Order By: Relevance
“…Surface roughness evaluation is required for describing functional behavior and monitoring product quality [2]. Furthermore, it is a crucial characteristic in many fundamental industrial concerns, such as friction [3], adhesion [4], electrochemical potential [5][6], aesthetic appearance [7], as well as positional accuracy [8]. As an outcome, many experimental and theoretical studies have been conducted on surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness evaluation is required for describing functional behavior and monitoring product quality [2]. Furthermore, it is a crucial characteristic in many fundamental industrial concerns, such as friction [3], adhesion [4], electrochemical potential [5][6], aesthetic appearance [7], as well as positional accuracy [8]. As an outcome, many experimental and theoretical studies have been conducted on surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Under clinical conditions, thermal, chemical, and mechanical factors affect the quality, esthetics and longevity of ceramic restorations [14]. The complex interaction of food, beverages, saliva, and fluoride interaction of toothpaste with tooth brushing has previously demonstrated changes in the surface of ceramic materials in terms of volume, gloss, characterization, and hardness, resulting in low durability [16], [21], [22]. Therefore, tests such as tooth-brushing simulation can help to gain insight into the clinical performance of these materials [14], [23].…”
Section: Discussionmentioning
confidence: 99%
“…These clusters were made up of small spherical fillers (10 nm) and large core fillers (1–3 μm) [ 14 ]. Research has demonstrated that the amount and type of the organic matrix have an impact on the roughness values [ 2 , 23 ]. Because materials’ molecular hardness values may be impacted by variations in the polymerization ratios of UDMA and Bis-GMA.…”
Section: Discussionmentioning
confidence: 99%
“…Surface roughness explains the impact of pre-treatment techniques on the surface morphology of the material [ 1 , 13 ]. Surface roughness is often expressed as (Ra), which represents the average of the microscopic peaks and valleys of the measured surface [ 23 ].…”
Section: Introductionmentioning
confidence: 99%